Characterization of Brazilian floral honey produced in the states of Santa Catarina and São Paulo using quantitative nuclear magnetic resonance (qNMR) spectroscopy - Aline Nunes; Mauricio Luis Sforça; Silvana Aparecida Rocco; Gadiel Zilto Azevedo; Beatriz Rocha dos Santos; Cristine Vanz Borges; Giuseppina Pace Pereira Lima; Sidnei Moura; Marcelo Maraschin (Food Chemistry Advances, 2023)
This study applied qNMR spectroscopy and chemometrics to metabolically profile polyfloral honey samples collected in southeastern (São Paulo - SP) and southern (Santa Catarina - SC) Brazil, over the 2019–2020 and 2020–2021 harvest seasons. Both 1D and 2D NMR experiments were carried out to identify and quantify metabolites, followed by descriptive statistical analysis, heatmap, and principal component analysis (PCA), considering geographic and botanical origins. Twenty-one metabolites were detected, encompassing carbohydrates, amino acids, organic acids, ketones, alcohols, esters, and alkaloids. The heatmap and the PCA allowed for distinguishing the geographical and botanical origin. Regarding the botanical origin, three clusters were detected, i.e., Hovenia dulcis (SC), Citrus spp. (SP), and Eucalyptus spp. (SC and SP). The analytical approach proved to be effective for determining the geographic and botanical origins of Brazilian polyfloral honey, even though the country has a huge floral diversity and, accordingly, different types of honey.